Properties of Oriented Strand Board Prepared from Steam Treated Bamboo Strands under Various Adhesive Combinations - Adrin Adrin; Fauzi Febrianto; Sucahyo Sadiyo (Masyarakat Peneliti Kayu Indonesia, 2013)
The objectives of this research were to analyze the physical and mechanical properties of Oriented Strand Board (OSB) prepared from steam treated betung bamboo (Dendrocalamus asper) strands under various adhesive combinations. The strands were steamed at 126 °C for 1 h with the pressure of 1.4 kg cm-2 prior to be blended with adhesive. Three-layered OSBs with the core layer orientation perpendicular to the face layers were prepared by bonding using 5% methylene diphenyl diisocyanate (ISO), 7% phenol formaldehyde (PF), combination of ISO:PF:ISO and PF:ISO:PF adhesives. Paraffin in amount of 1% was added as an additive. The strand ratio for face, core, and back layers was 1:1:1, respectively.The results indicated that the physical properties i.e., water absorption and thickness swelling, and mechanical properties i.e., modulus of rupture and modulus of elasticity both parallel and perpendicular to the grain direction and internal bond of OSB bonded ISO and combination of ISO:PF:ISO adhesives were much better than that of bonded with combination PF:ISO:PF and PF adhesives. Almost all parameters of OSB tested in this experiment were higher than the minimum criteria requirement of CSA 0437.0 (Grade 0-2) standard, except the value of MOE perpendicular to the grain direction of OSB bonded with PF adhesive.Key words: betung bamboo, isocyanate, oriented strand board, phenol formaldehyde, steam